2007
DOI: 10.1590/s0004-27492007000600013
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da cinética do epitélio corneano com marcadores de proliferação celular

Abstract: The markers BrdU, Ki-67 and AgNOR showed a positive correlation with statistical significance among the cellular proliferation situations studied (control, hypoproliferation and hyperproliferation); the AgNOR did not show statistically significant differences among the control and hypoproliferation situations and there was more agreement in the results among markers BrdU and Ki-67 in three cell proliferation situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
2
8
0
1
Order By: Relevance
“…The half-life of Ki67 is short (less than one hour after mitosis). Thus, the use of Ki67 antibody guarantees that only cells that have completed the cell cycle are stained (CRESTA & ALVES, 2007;PAULY et al, 2009), a fact observed in the present study.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The half-life of Ki67 is short (less than one hour after mitosis). Thus, the use of Ki67 antibody guarantees that only cells that have completed the cell cycle are stained (CRESTA & ALVES, 2007;PAULY et al, 2009), a fact observed in the present study.…”
Section: Discussionsupporting
confidence: 63%
“…Different methods are available for the evaluation of cell proliferation during inflammation (WILSON et al, 2001;BALDWIN & MARSHALL, 2002;PAULY et al, 2009). Ki67 has been shown to be a useful marker for the investigation of cell proliferation in corneal epithelium and stroma of rabbits (CRESTA & ALVES, 2007;PAULY et al, 2009). During corneal wound healing, the epithelium migrates, proliferates and reestablishes its adhesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose to study the corneas of rabbits due to their similarity to the human cornea. They have [21][22][23] . MMC, a drug used as adjuvant therapy in many ophthalmic procedures, acts as an inhibitor of cell proliferation and has been linked to postoperative complications such as corneal erosion, conjunctival hyperaemia, blepharospasm, corneal and scleral thinning, and perforations 8,10 .…”
Section: Discussionmentioning
confidence: 99%
“…Sections (4-µm) were stained using hematoxylineosin (HE) or subjected to immunohistochemistry to detect cell proliferation (Ki-67 [clone MIB-1]; DAKO, CA, USA) (CRESTA & ALVES, 2007). Optimum dilution of the antibody was 1:50.…”
Section: Histopathology and Immunohistochemistrymentioning
confidence: 99%